Perancangan Sistem Informasi Pencapaian Karyawan Menggunakan Model Waterfall Berbasis Web di PT Inkara Sejahtera Utama Bandung - Rizwan Azqi Zaenudin Azis; Johni Pasaribu; Muhamad Roni (LPPM STMIK IKMI Cirebon, 2022)
PT Inkara Sejahtera Utama Sejahtera is located at Bumi Adipura, Jl. Palem I no 5 Gedebage Bandung City is a company engaged in the event organizer. In carrying out their work, employees need an employee achievement information system, namely a system that can manage the work of employees and the time of work that must be in accordance with the work schedule provided by PT Inkara Sejahtera Utama Bandung. However, the problems encountered by the system used are still using a manual system so that workers still have to fill out forms provided by the company to make reports to the company's leadership and can also cause file accumulation in the company. This study uses a qualitative descriptive technique to explain the existing objective situation, while for software development it is carried out using the SDLC (Software Development Life Cycle) model waterfall method with black box testing. The design of this software is done using HTML, PHP, Boostrap, MySQL and databases to create a web-based employee achievement information system. This web-based Employee Achievement Information System can help employees and leaders in terms of knowing and monitoring the results of the work given by the leadership, and this web is intended to make it easier for employees and leaders to determine the results of work that has been done by employees